Prohibition of Alms Distribution to Ahl al-Bayt: (Study of Asbābu Wurūd Al-Hadīth and Its Implications for Islamic Maqasid) - Furqan Ar-Rasyid (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2025)
One of the objectives of Zakat recitation is the creation of Islamic social justice. Zakat which is intended for the senifs is considered as a solution to overcome the burden of the poor and also as a form of caring for others. The reality that we face is that there are Muslims in general and from the Sayid and Syarifah groups in particular who have not enjoyed the sharia maqāsid and the wisdom of sharia zakat distribution evenly, even though among them there are poor and even needy. The problem lies in the prohibition of receiving zakat because they are descendants of the Prophet Muhammad (Ahl al-Bayt) who are not allowed to accept any property except gifts, even though there are those who live in need and are juxtaposed with the same position as the needy or poor. This study aims: First, to describe and explain the Ahl al-Bayt referred to by presenting several meanings according to Fuqahā, including raising and analyzing several hadiths that prohibit the distribution of zakat to them; both in terms of Asbābu al-Wurūd and the socio-historical society of Medina at that time. Next compare with some verses of the Quran that explains the provisions and priorities of the distribution of Zakat to the Poor and Poor. Second, finding an adequate explanation of the Asbāb Musabbab prohibition, the third looks at the presence or absence of opportunities for the use of Zakat by them today because of their poverty or poverty, so that the purpose of Zakat reconciliation itself can be felt by the poor in a fair and equitable manner without any looking at any status. This research uses the tahlīlī method, by conducting a study of the prophetic hadith along with the analysis of the context of the verse and a coherent hadith combined with some references and views of the ulamā and its application in the present context